THE EFFECT OF THE CONTEXTUAL TEACHING AND LEARNING APPROACH ON STUDENTS' PHYSICS LEARNING OUTCOMES STATE JUNIOR HIGH SCHOOL 2 KUTACANE - Fitri Handayani; Rayani; Desy Maya Sari (Jurnal Penelitian Progresif, 2024)
The Contextual Teaching And Learning approach is a learning concept that helps teachers relate the material taught to students' real-world situations and encourages the knowledge they have with its application in their daily lives. The main objective of this study was to obtain data on physics learning outcomes and to determine the effect of the Contextual Teaching And Learning approach on students' physics learning outcomes in class VIII semester II of SMP Negeri 2 Kutacane. This study was conducted in class VIII semester II of SMP Negeri 2 Kutacane on the subject of Sound. The population of this study was all 200 class VIII students, while the research sample was 40 people. In this study, the normality test of the scores of the student groups who received the Contextual Teaching And Learning approach each obtained a price of L o = 0.1179 , while L = 0.190 and the Direct Instruction learning model (Direct Learning) L o = 0.9871, L = 0.190 means that the two sample groups above come from a normally distributed population. For the F test, the F count value = 4.28 and F table = 18.05 or F count < F table means that both samples are homogeneous. From the calculation results, t count = 5.47 and t table = 1.68 means t count > t table , so the hypothesis is accepted. In other words, the data shows that the learning outcomes of students from the group that received teaching with the Contextual Teaching And Learning approach were better than the learning outcomes given Direct learning.